After dark - Murakami, Haruki (London : Vintage Books, 2008)
Eyes mark the shape of the city The midnight hour approaches in an almost-empty diner. Mari sips her coffee and reads a book, but soon her solitude is disturbed: a girl has been beaten up at the Alphaville hotel, and needs Mari's help.
Keywords: Sisters -- Fiction; Models (Persons) -- Fiction; Students -- Fiction